Regionalizing a Tourism Satellite Account: A top-down approach based on existing data sources - Frenţ, Cristi (Publishing House of Wroclaw University of Economics and Business, 2023)
Purpose: Developing Tourism Satellite Account (TSA) at regional level is a challenging task for any country that wishes to have data for its component regions or its sub-national entities. There are numerous conceptual and methodological issues to be faced in such an endeavour. Considering data availability, particularly the lack of demand-side data at regional level, the purpose of this paper was to employ a top-down method for regionalizing TSA data in Romania at the level of its eight development regions. Design/methodology/approach: This method is based on using multiple regional indicators and existing data sources coming from the supply side: tourism statistics, passenger transport statistics, culture statistics, administrative data, structural business survey, labour cost survey, as well as national and regional accounts. Findings: Regionalizing TSA was obtained but restricted only to calculating the TSA aggregates at regional level. Originality: This paper will contribute to enhancing the TSA development at sub-national (regional) level by proposing a quick top-down method based only on the existing data sources. Research limitations/implications: The major limitation is the lack of a direct reconciliation of data between regional supply and regional demand which is actually the philosophy of any TSA. Practical implications: The regionalization of TSA data proposed in this paper can be illustrative for countries having national TSAs and wishing to make advancements at sub-national (regional) level.
Argumenta Oeconomica, 2023, Nr 1 (50), s. 205-226
Keywords: tourism satellite account; regional tourism satellite account; top-down approach; regionalization; regional statistics; Romania